Development of an ombrotrophic peat bog (low ash) reference material for the determination of elemental concentrations - Yafa, Charun; Farmer, J. G.; Graham, M. C.; Bacon, J. R.; Barbante, C.; Cairns, W. R. L.; Bindler, R.; Renberg, I.; Cheburkin, Andriy K.; Emons, H.; Handley, M. J.; Norton, S. A.; et al. (Journal of environmental monitoring, 2004)
Given the increasing interest in using peat bogs as archives of atmospheric metal deposition, the lack of validated sample preparation methods and suitable certified reference materials has hindered not only the quality assurance of the generated analytical data but also the interpretation and comparison of peat core metal profiles from different laboratories in the international community. Reference materials play an important role in the evaluation of the accuracy of analytical results and are essential parts of good laboratory practice. An ombrotrophic peat bog reference material has been developed by 14 laboratories from nine countries in an inter-laboratory comparison between February and October 2002. The material has been characterised for both acid-extractable and total concentrations of a range of elements, including Al, As, Ca, Cd, Cr, Cu, Fe, Hg, Mg, Mn, Na, Ni, P, Pb, Ti, V and Zn. The steps involved in the production of the reference material (i.e. collection and preparation, homogeneity and stability studies, and certification) are described in detail.